Diseño del sistema de gestión de calidad basado en la norma NTC ISO 9001:2015 en la empresa MonguiGol del municipio Monguí. (2023)
This research project is based on the approach of a quality management system based on the international standard ISO 9001:2015, for the operational part of the soccer ball manufacturing in the MonguiGol Company. It starts with the collection of information on internal processes and data related to the production procedures carried out by the company, then a diagnosis of the company's compliance with the requirements of the ISO 9001:2015 standard is made, that is, the data using a survey of senior management regarding inherent compliance with what is stated in the standard.